Medical pluralism for community health in Thammasen sub-district, Photharam district, Ratchaburi province, Thailand - Wipanun Muangsakul; Sunti Srisuantang; Ravee Sajjasophon (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - When reviewing Community Health Development, it is necessary to understand the community context, including community health and details of medical pluralism (MP). The purpose of this paper is to correlate and predict between community health and related factors and delineate phenomenon of MP in Thammasen, Ratchaburi province, Thailand. Design/methodology/approach - A mixed-methods sequential explanatory design was applied in this research. The quantitative survey was conducted by using an interview questionnaire. The 400 respondents were selected by simple random sampling from 11 villages. For the qualitative study, in-depth interviews were conducted with 37 key informants from selected health professionals, folk healers and local leaders. Findings - The respondents were 56.5 percent female with a mean age of 53.8 years. The factors relating to community health included: health care behaviors, perceived health status, attitudes toward health care and access to health services. Considering the four predictive variables as a group revealed a 26.2 percent variation in community health. The phenomenon of MP was covered by the following three main aspects: self-health care (SHC)-healthy people pay attention to self-care and used herbal remedies to reduce early symptoms; folk medicine (FM)-some folk healers provide holistic healing, use herbal remedies and transfer knowledge to people who are interested and professional medicine (PM)-some health professionals adopt the concept of integrated medicines such as recommending that patients practice SHC and promote the use of Thai traditional medicine (TTM) and complementary and alternative medicine (CAM). Originality/value - Health professionals, folk healers and local leaders should provide effective action domains that focus on the following four factors of community health: effective health care behavior, concern for health status, positive attitudes toward health care and accessibility to health services. Regarding MP, integrated medical and health care models should be developed to link SHC, FM and PM (including TTM/CAM).